Novel method of generating water-in-oil(W∕O) droplets in a microchannel with grooved walls - Kim, Jihoon (American Institute of Physics, 2011)
We present a novel method of generating and retrieving droplets stored in microfluidic grooves or cavity structures. First we designed and fabricated polydimethylsiloxane microchannels with grooves on the walls and then produced a two-phase flow of oil and aqueous phases to form aqueous phase droplets in an oil state. We propose the following three mechanisms of droplet generation: the contact line on the groove wall continues moving along the wall and descends to the bottom of the cavity, confining the aqueous phase in the cavity; once the interface between the oil and aqueous phases moves into the cavity, the interface contacts the top of the neighboring groove; and a spherical droplet forms at the corner in the cavity due to surface tension. The viscosity of the oil phase and the surface tension of the interface determine whether a droplet can be generated. Then, we could adjust the velocity of the interface and the aspect ratio of the cavity to achieve the optimal conditions for generating the single droplet. We observed that the largest droplet is stably generated without a daughter droplet at typical values of free-stream velocity (10 μl∕min) and groove pitch 110 μm for all three cases with different oil phases (20, 50, and 84 cP). This technique is expected to serve as a platform for droplet-based reaction systems, particularly with regard to monitoring cell behavior, in vitro expression, and possibly even micropolymerase chain reaction chambers.